Deteksi dan Identifikasi Mikroorganisme Terbawa Benih Cabai Rawit (Capsicum frutescens L.) yang dijual pada Marketplace - Stepangel Mighty Graceia; Suskandini Ratih Dirmawati; Muhammad Nurdin; Titik Nur Aeny (Universitas Lampung, 2026)
Seed quality is a critical factor in achieving optimal crop yield. Cayenne pepper (Capsicum frutescens L.) seeds are widely obtained through marketplaces; however, information on seed-borne microorganisms associated with commercially sold seeds remains limited. This study aimed to detect and identify microorganisms carried by cayenne pepper seeds marketed through local marketplaces. In this research, five seed varieties obtained from the marketplace were examined, namely KSD 108, Top Garden Seed, Red Cluster Pepper, Raja, and Home Garden. Seed health testing was performed using seed washing, blotter paper incubation, and agar plate methods. Observed variables included seed germination percentage, incidence of microbial infection, fungal identification based on microscopic characteristics, and bacterial identification using the 3% KOH Gram test, soft rot assay, and hypersensitive reaction test. Data were analyzed descriptively and presented in tables and figures. The results showed that uncertified seeds—Top Garden Seed, Red Cluster Pepper, Raja, and Home Garden—were contaminated by various seed-borne microorganisms, predominantly Aspergillus niger, A. fumigatus, A. tamarii, Fusarium oxysporum, and F. verticillioides. Gram-negative bacteria were also detected. In contrast, certified seeds contained A. niger and Gram-positive bacteria.